Notions of popular culture in cultural policy: a comparative history of France and Britain - Looseley, David (International Journal of Cultural Policy, 2011)
The Devlin and Hoyle report, Committing to culture: arts funding in France and Britain, argues that the cultural policies of these two European neighbours have been steadily converging since the mid‐1990s but that their social and economic contexts are now quite different (e.g. youth unemployment, GDP, disposable income). The paper addresses this convergence‐within‐divergence by comparing how policy discourses have conceptualised popular culture in the two countries. It investigates the hypothesis that, in both, an engagement with popular culture has in fact been an important driver of change, albeit at different times and with different taxonomies. And it asks what light this comparison might shed on cultural policy thinking in the twenty‐first century.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2010.541907
Keywords: France; UK; cultural policy; history; popular culture